National dental health month in West Sumatera - Zola, Febri (BKM Public Health and Community Medicine, 2021)
Access to dental care People from West Sumatra who receive dental care from medical personnel around 35.3 percent. More than half of the Sumbar community has not received treatment because of inadequate facilities and access to services. People in rural areas have more difficulty getting dental health services than in cities. National dental health month activities One of the dental health programs are the National Dental Health Month (BKGN), which conducts dental check-ups, tooth fillings, tooth extractions, tartar cleaning, and free dental education. However, this activity is carried out once a year, and the target is only 1,000 people. This program should be followed up with a dental health program held at least once a month or twice a month. The target of this program must also be evenly distributed to remote areas of West Sumatra. Providing free toothbrushes for the less fortunate. Conducting dental health education and providing free toothbrushes and toothpaste to the community so that people can practice oral health in their respective homes. Village heads and cadres The village Head can gather residents to be given information about the dental health program that will be carried out. Apart from the village head, cadres can also be involved in providing dental health training so that these cadres can provide education about dental health to the community. Dental health month, which is followed up with the community dental health program National Dental Health Month (BKGN), held once a year, must be followed up with a monthly healthy teeth program. This program includes education about dental health, free dental examinations, free tartar cleaning, free dental fillings, and free tooth extraction. This puskesmas program also moves to the people's homes, making the program more evenly distributed. The evaluation of this program is carried out once a month through a dental examination and an examination of their toothbrushes at home.